Health and Economic Outcomes Associated with Use of an Antimicrobial Envelope as a Standard of Care for Cardiac Implantable Electronic Device Implantation. (25th May 2015) - SHARIFF, NASIR; EBY, ELIZABETH; ADELSTEIN, EVAN; JAIN, SANDEEP; SHALABY, ALAA; SABA, SAMIR; WANG, NORMAN C.; SCHWARTZMAN, DAVID
Outcomes with Routine Use of Antimicrobial Envelope Introduction Infection of cardiac implanted electrical devices (CIED) is a problem. In selected patients, use of an "antibacterial envelope" (AIGISRx®) is associated with low CIED infection rates. The value of this device when used as a standard of care is unclear. Methods and Results Retrospective analysis of all patients (N = 1, 476) who underwent CIED implantation at a single hospital. During the study period, some implanters used the AIGISRx as a standard of care (Yes‐AIGISRx Group, N = 365), whereas others did not use it at all (No‐AIGISRx Group, N = 1, 111). A risk score based on preoperative factors was calculated for each patient. Rates of CIED infection within 6 months were measured, and associated costs were estimated. The Yes‐AIGISRx and No‐AIGISRx groups had similar preoperative infection risk. In the No‐AIGISRx group, 19 infections were observed (1.7%), versus 0 in the Yes‐AIGISRx group (P = 0.006). The 6‐month mortality rate among patients with infection was significantly greater than among those without infection (15.7% vs. 4.5%, P = 0.021). The average hospital duration for infection care was 13 days. By extrapolating the infection rate and costs observed in the No‐AIGISRx group to the Yes‐AIGISRx group, we estimated that there would have been 6.2 additional infections costing approximately $340, 000. This cost was similar to the actual cost of the devices in the Yes‐AIGISRx group, estimated at $320, 000. Conclusions Standard of care use of an antibacterial envelope as a standard of care was associated with a significantly lower rate of CIED infection, and appeared to be economically reasonable. Prospective trials to address these findings may be worthwhile.